ERRORS AND FRAUD IN ACCOUNTING. THE ROLE OF EXTERNAL AUDIT IN FIGHTING CORRUPTION - Ionescu, Luminita (Annals of Spiru Haret University. Economic Series, 2017)
Accounting errors and fraud are common in most businesses, but there is a difference between fraud and misinterpretation of communication or accounting regulations. The role of management in preventing fraud becomes important in the last decades and the importance of auditing in curbing corruption is increasingly revealed. There is a strong connection between fraud and corruption, accelerated by electronic systems and modern platforms. The most recent developments tend to confirm that external auditing is curbing corruption, due to international accounting and auditing standards at national and regional levels. Thus, a better implementation of accounting standards and high quality of external control could prevent errors and fraud in accounting, and reduce corruption, as well. The aim of this paper is to present some particular aspects of errors and fraud in accounting, and how external audit could ensure accuracy and accountability in financial reporting.